Relationship of staphylococcal toxins and enzymes with serological and phage types - Choudhuri, K. K. (1970)
A study has been made of 523 strains of staphylococci on the basis of biological properties, phage typing, and serology. The value of serology in the identification of pathogenic staphylococci has been assessed.